Selective albumin-binding surfaces modified with a thrombin-inhibiting peptide - Sidonio C Freitas (2014)
Blood-contacting medical devices have been associated with severe clinical complications, such as thrombus formation, triggered by the activation of the coagulation cascade due to the adsorption of certain plasma proteins on the surface of biomaterials. Hence, the coating of such surfaces with antithrombotic agents has been used to increase biomaterial haemocompatibility. Biomaterial-induced clotting may also be decreased by albumin adsorption from blood plasma in a selective and reversible way, since this protein is not involved in the coagulation cascade. In this context, this paper reports that the immobilization of the thrombin inhibitor D-Phe-Pro-D-Arg-D-Thr-CONH2 (fPrt) onto nanostructured surfaces induces selective and reversible adsorption of albumin, delaying the clotting time when compared to peptide-free surfaces. fPrt, synthesized with two glycine residues attached to the N-terminus (GGfPrt), was covalently immobilized onto self-assembled monolayers (SAMs) having different ratios of carboxylate-hexa(ethylene glycol)- and tri(ethylene glycol)-terminated thiols (EG6-COOH/EG3) that were specifically designed to control GGfPrt orientation, exposure and density at the molecular level. In solution, GGfPrt was able to inactivate the enzymatic activity of thrombin and to delay plasma clotting time in a concentration-dependent way. After surface immobilization, and independently of its concentration, GGfPrt lost its selectivity to thrombin and its capacity to inhibit thrombin enzymatic activity against the chromogenic substrate n-p-tosyl-Gly-Pro-Arg-p-nitroanilide. Nevertheless, surfaces with low concentrations of GGfPrt could delay the capacity of adsorbed thrombin to cleave fibrinogen. In contrast, GGfPrt immobilized in high concentrations was found to induce the procoagulant activity of the adsorbed thrombin. However, all surfaces containing GGfPrt have a plasma clotting time similar to the negative control (empty polystyrene wells), showing resistance to coagulation, which is explained by its capacity to adsorb albumin in a selective and reversible way. This work opens new perspectives to the improvement of the haemocompatibility of blood-contacting medical devices.